Cardiovascular origins of preeclampsia. Issue 6 (December 2017) - Kalafat, Erkan; Thilaganathan, Basky
Abstract : Purpose of review: To review the current data on maternal cardiovascular adaptation in normal pregnancy and preeclampsia. Recent findings: Defective placentation causes early-onset preeclampsia, a disease entity that is considered more or less distinct from late-onset preeclampsia. The latter has been attributed as 'maternal' preeclampsia. There are inconsistencies with the placental origins hypothesis, especially when considering the lack of a causative association with abnormal placental histology or impaired fetal growth. An alternative explanation is that placental dysfunction is secondary to maternal cardiovascular maladaptation in pregnancy. The concept that placental dysfunction is secondary to a maternal disorder is not new when one considers the clinical similarities between preeclampsia and gestational diabetes – both pregnancy-specific conditions that are cured by birth. It is accepted that gestational diabetes develops when the maternal pancreas is unable to manage the increasing glucose load of pregnancy. It is now apparent that pregnancy presents a substantial cardiovascular load on the maternal heart, and that cardiovascular dysfunction precedes the disorder, predominates in the clinical syndrome and persists for several decades postpartum. It is time to consider the evidence that failure of the maternal cardiovascular system to adapt to pregnancy may well be the primary mechanism leading to secondary placental dysfunction in preeclampsia. Summary: Many of the existing paradoxes of preeclampsia challenge the placental origin hypothesis and are explained if one considered preeclampsia to be a cardiovascular syndrome.